Analysis of factors influencing tumor volume doubling time in hepatocellular carcinoma and its predictive value for progression-free survival - Ting Huang; Yong Chen (Scientific Reports)
Abstract This study aims to identify and analyze the factors that affect tumor volume doubling time (TVDT) in hepatocellular carcinoma (HCC) and evaluate how these factors impact progression-free survival. We performed a retrospective study on 183 confirmed cases of HCC at the General Hospital of Ningxia Medical University from January 1, 2018, to December 31, 2023. We utilized 3D Slicer 5.1.0 to segment the region of interest slice by slice. Then, we calculated the tumor volume using the segment statistics. We calculated the TVDT using the equation: TVDT = [(T - T0) ln2]/[ln(V/V0)]. We analyzed several factors that might affect TVDT through logistic regression. These factors included age, gender, etiology, Child-Pugh classes, ascites, hepatic encephalopathy (HE), portal vein tumor thrombus (PVTT), alpha-fetoprotein (AFP), albumin-to-globulin ratio (AGR), bilirubin, AST/ALT, hemoglobin (Hb), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and BCLC stage. Subsequently, we examined the factors that could influence the progression-free survival of HCC, including TVDT, age, gender, etiology, Child-Pugh classes, ascites, HE, PVTT, AFP, AGR, bilirubin, AST/ALT levels, Hb, NLR, PLR, BCLC stage and locoregional therapy (LT). We used the Kaplan-Meier method for univariate analysis and the Cox proportional hazards regression model for both multivariate analysis and interaction analysis. This study analyzed 183 patients with HCC. Of the 183 patients, 146 (79.8%) were male and 37 (20.2%) were female. The mean age of the patients was 57.92 years, with a standard deviation of 9.75 years. The median TVDT was 76.77 days (IQR 43.66-169.55 days). The 183 patients were divided into two groups based on a cutoff value of 120 days: those classified as having slow growth (TVDT > 120 days) and those classified as having rapid growth (TVDT ≤ 120 days). 119 (65.03%) patients were in the rapid growth group, while 64 (34.97%) patients were in the slow growth group. AFP levels were higher in the rapid growth group compared to the slow growth group. A higher proportion of patients in the rapid growth group underwent LT compared to those in the slow growth group (P < 0.05). Univariate logistic regression indicated that higher AFP levels were associated with a shorter TVDT. Kaplan-Meier analysis revealed that TVDT, AFP, Child-Pugh classes, PVTT, ascites, age, NLR, PLR, Hb, BCLC stage, and LT are all correlated with progression-free survival (P < 0.05). Multivariate Cox regression indicated that TVDT, AFP, LT, and BCLC stage were independent risk factors for progression-free survival (P < 0.05). The interaction analysis demonstrated that TVDT did not correlate with AFP, LT, or BCLC stage (P > 0.05). Higher AFP levels are associated with a shorter TVDT, potentially acting as an independent risk factor for progression-free survival in HCC. Combining the TVDT, AFP levels, BCLC stage, and LT offers a more accurate prediction of progression-free survival in HCC patients.